Pembelajaran Berbasis Outdoor Learning dengan Metode Eksperimen Ice cream carica untuk Meningkatkan Pemahaman Konsep IPA Siswa - Maulina Damayanti; Firdaus; Pamungkas Stiya Mulyani (Mataram University, 2026)
This study aims to determine the difference in students' science concept understanding between classes taught using an outdoor learning-based model through the experimental method of making carica ice cream and classes using a conventional learning model. This quantitative research used a Quasi-Experimental design with a Nonequivalent Control Group Design model. The research population included all seventh-grade students at SMPN 3 Mojotengah in the 2026/2027 academic year, with the sample selected using purposive sampling. Class VII A was designated as the experimental class (N=32) and class VII B as the control class (N=32). Data collection instruments consisted of objective tests (Pretest and Posttest ) and observation sheets. Data were quantitatively analyzed through parametric statistical tests using SPSS. The hypothesis testing results using the Independent Sample T-Test obtained a significance value (2-tailed) of 0.001 (p < 0.05), indicating a highly significant difference in the improvement of science concept understanding between the two groups. Furthermore, the effectiveness analysis using the Normalized Gain (N-Gain) test showed that the experimental class achieved an average score of 0.67 (medium to high category), while the control class only achieved a score of 0.53 (medium category). The conclusion of this study is that the implementation of the outdoor learning-based model through the experiment of making carica ice cream is proven to be significantly more effective and meaningful in improving students' science concept understanding on the topic of temperature, heat, and phase changes compared to conventional methods.